The Effect of Exposure Density on EFL Learners' Fluency in Saudi Arabia - Ibrahim, Intisar Zakariya Ahmed (International Journal of Language and Literary Studies, 2023)
The Internet proliferation, information technology, and globalization as well as the importance of English as a global language cannot be overstated. It is widely recognized that Saudi university students, learning English as a foreign language, encounter numerous learning challenges stemming from various factors. This paper delves into the critical issue of English language exposure and postulates that inadequate exposure to English is a central contributor to students' learning difficulties. To investigate this, a questionnaire was administered to a cohort of 50 students, comprising both male and female participants enrolled in the Department of English and Translation at the University of Qassim. The findings from the survey revealed that, on average, the students reported moderate exposure to the English language. Additionally, the data indicated a noteworthy disparity, with male students exhibiting greater exposure to English compared to their female counterparts. These results serve as a preliminary exploration of the issue of English language exposure among Saudi university students. They underscore the need for further in-depth research in this area to comprehensively understand the dynamics of language exposure and its impact on the learning experiences of EFL (English as a Foreign Language) learners. This concludes by suggesting the imperative for future research endeavours and outlining initial recommendations for augmenting language exposure among EFL learners. These recommendations aim to inform pedagogical practices and strategies that can enhance English language learning in the context of Saudi Arabian universities.